WHY WOMEN INVOLVEMENT IN MAKING ONLINE LEARNING POLICIES FOR ELEMENTARY SCHOOL IS MINIMAL? - Akbar, Moh. Rifaldi; Zahra, Fina; Sukmawati, Dian; Kristina, Dina; Suciati, Titis Nurwulan (Marwah: Jurnal Perempuan, Agama dan Jender, 2025)
The Covid-19 pandemic reshaped schooling by shifting educational responsibilities from classrooms to homes, placing a concentrated load on women. In the suburban areas of Bekasi, Greater Jakarta, mothers and older sisters became the primary supervisors of elementary school children’s online learning while managing everyday household demands. Yet, thier experiences and insights rarely appear in regional education policies. This research examines how women handled the intensified tasks of supporting elementary-level online learning and explores the factors that limit their involvement in policy discussions. Elementary students were selected because their learning requires close and continuous supervision. Using a qualitative design, the research draws on focus group discussions and in-depth semi-structured interviews, followed by a three-stage coding analysis. The findings identify three key factors shaping women’s limited policymaking presence. (1) Ideological factors stem from persistent assumptions that public decision-making is not a women’s domain. (2) Internal factors arise from tensions and emotional demands within the household. (3) External factors include social expectations and institutional arrangements that expand women’s physical and mental workload. By documenting these layered pressures, the study demonstrates how women become the primary actors sustaining emergency education while remaining structurally sidelined from policy arenas. The analysis offers empirical insight into the gendered dynamics of home-based schooling in suburban Global South contexts.